EFFECTS OF PARTIALLY HYDROGENATED PYRIDINES (CYANOTHIOACETAMIDE DERIVATIVES) ON THE BLOOD OF RATS WITH COMBINED PARACETAMOL-ALCOHOLIC LIVER INJURY - Elena Yu. Bibik; Bogdan S. Krivokolysko; Anna A. Burdeynaya; Andrey V. Demenko; Konstantin A. Frolov; Viktor V. Dotsenko; Sergey G. Krivokolysko (Кубанский научный медицинский вестник, 2019)
Aim. In this research, we studied the parameters of blood biochemical analysis in rats with combined paracetamol-alcoholic liver injury after its pharmacological correction by newly synthesized partially hydrogenated pyridines (cyanothioacetamide derivatives).Materials and methods. 50 samples of new derivatives of partially hydrogenated pyridines synthesized on the basis of the “Chemex” Research Laboratory of the Vladimir Dal’ Lugansk National University underwent virtual bioscreening, which allowed the selection of 4 compounds, the biological activity of which may be associated with the effect on the protein synthesis and detoxifi cation function of the liver. The experiment was conducted on 48 white outbred male rats. For 14 days, the rats of the control and experimental groups were intragastrically injected with 1 ml of 40% ethanol and paracetamol at a dose of 500 mg/kg once a day. Pharmacocorrection with a thiotriazoline reference drug (50 mg/kg) and pyridine derivatives at a dose of 5 mg/kg was performed from the fourth day. On the 15th day, blood was sampled to determine the level of total bilirubin, alanine aminotransferase, aspartate aminotransferase and thymol turbidity test.Results. The value of total bilirubin in the blood of the rats treated with CV046 compounds was 34.88% lower than that in the control group. The animals of the test groups receiving CV047 also showed signifi cant differences with the control group in terms of bilirubin level (a decrease of 31.78%). The AST values in the blood of rats in the test groups had no signifi cant differences as compared with intact animals. Following 10 days of pharmacological correction of combined paracetamol-alcoholic liver injury with CV146, the total bilirubin level in the blood decreased by 26.36% in comparison with the control group, with the activity of ALT and AST demonstrating the levels of intact values.Conclusions. The conducted screening studies of four partially hydrogenated pyridines — cyanothioacetamide derivatives — using the model of combined paracetamol-alcoholic liver injury when used at a dose of 5 mg/kg during ten days have shown a high hepatoprotective and detoxifying activity of the following three compounds: СV046 (2-[(9-tert-butyl-1,5-dicyano4-oxo-3-azaspiro[5,5]undec-1-en-2-yl)thio]-N-(2-ethylphenyl)acetamide — IUPAC), СV047 (2-[(9-tert-butyl-1,5-dicyano-4-oxo-3-azaspiro[5,5]undec-1-en-2-yl)thio]-N-(4-fl uorophenyl) acetamide) and СV146 (benzyl 4-(4-chlorophenyl)-5-cyano-6-({2-[(3,4-dimethylphenyl)amino]-2-oxoethyl}thio)-2-methyl-1,4-dihydropyridine-3-carboxylate).